Systematic Eco-innovation in PSS - Pacheco, Diego A De J (2017)
Studies on PSS are emerging as a growing body of literature driven by the desire to reach economic aspects and sustainable resource management. Although recent studies have highlighted environmental benefits of PSS, insights about how companies can systematically obtain eco-innovations in PSS design, using only TRIZ or TRIZ combined with other methodologies, are still limited. In this sense, aiming to identify the state of the art eco-innovation practices with TRIZ in PSS, a literature review was conducted. Findings were accumulated in order to present the current research framework in this research field. Trends and research opportunities also were identified.